Defeating Communist Insurgency : Experience From Malaya and Vietnam - Thompson, Robert, 1916-1992 (London Chatto and Windus, 1974)
The 1st vol. of the author's trilogy ; the 2d of which is No exit from Vietnam ; the 3d, Revolutionary war in world strategy, 1945-1969.
Keywords: Malaya -- Vietnam -- Revolutions